Encouraging the participation and training of girls and women for engineering careers through university extension (Research, Society and Development, 2022)
The discrepancy that occurs between the number of women and men who study the various engineering courses in any higher education institution is notorious, despite the fact that there is a higher number of women in higher education courses in general. Based on data from the Brazilian higher education census, this article shows the current scenario of women in undergraduate courses, highlighting female representation in engineering, through a qualitative and quantitative research. It also includes the description of an extension project developed by the Federal University of Paraíba, that aims to arouse the interest of young women to enter engineering careers and to encourage undergraduate students who are already in these courses to persist, showing engineering as a profession promise, without gender distinction. It is expected that women encourage and are encouraged to continue in this career avoiding university evasion and increasing the representativity of women in the technological and scientific development in Brazil. This project idea has the purpose to contribute to a fairer and more equal society for men and women, where the choice of a career is achieved and developed with full potential, capacity, discernment, and without prejudice, avoiding a distinction of salary between genders.